The Effect of Video Project-Based Learning on Students' Critical Thinking Skills during the Covid-19 Pandemic - Albi Anggito; Pratiwi Pujiastuti; Dhiniaty Gularso (AL-ISHLAH: Jurnal Pendidikan, 2021)
Project-based Learning using video is being used at the University of Yogyakarta in order to examine the impact on students' thinking skills. The Paired Sample t-test analytic method was employed in this study to conduct a quasi-experiment, which is described in detail below. The findings revealed that: 1) the average increase from the pretest score to the posttest score was 4.55 in the experimental class and 3.41 in the control class, and 2) a statistically significant difference in the average increase was observed in the experimental class when the Project-based learning model was used in the classroom. The experimental class uses Project-based Learning, 3) the data in the experimental class is 0.097 (pretest) and 0.062 (posttest). In contrast, the data in the control class is 0.083 (pretest) and 0.064 (posttest), 4) the results of the hypothesis test revealed a significance level of 0. 007 in the experimental class and 0.016 in the control class, both of which were less than the significance level of 0.005, so that H0 was rejected and H1 was accepted. According to the findings of this study, there appears to be an effect of applying the Project-based learning model on students' critical thinking skills in social studies classes. PjBL (project-based learning) models that include video can help students substantially enhance their critical thinking skills.